Генеза гарантій прав та свобод людини й громадянина в Україні: історико-правове дослідження - Булавіна, С.; Bulavina, S. (Східноєвропейський національний університет імені Лесі Українки, 2019)
У статті досліджено історико-правову думку про гарантії прав і свобод людини та громадянина. Досліджено становлення та розвиток ідеї гарантій прав і свобод людини та громадянина в України. Встановлено, що на державу та її органи Конституція і закони України покладають обов’язки по забезпеченню прав і свобод людини та громадянина. Так, у ст. 3 Конституції України визначено головний зміст та спрямованість діяльності держави – права і свободи людини та їх гарантії. Історико-правові ідеї, висунуті видатними вченими, стали витоками і основою всіх суспільно-правових відносин, закріплення обов’язку держави захищати права і свободи людини, створили необхідні передумови для формування в суспільстві вимог гарантованості прав і свобод та поступового їх доповнення новими принципами та інститутами гарантій прав і свобод людини і громадянина.The article elucidates historical and legal views on the guarantees of the rights and freedoms of citizens, with a focus on the formation and development of the idea of guarantees of human and citizen's rights and freedoms in Ukraine. The author states that the responsibilities for the protection of human and citizen's rights and freedoms are vested in the Constitution, the state and its bodies, and the laws of Ukraine. Considering the thoughts and ideas of the representatives of the national historical and legal heritage, scholars point to their unprecedented contribution to the process of formation and development of such historical and legal category as guarantees of human rights and freedoms of citizens. It was preceded by a long and difficult way of origin and development of the idea of human and citizen's rights and freedoms and their guarantees. Historical and legal ideas, put forward by prominent scientists, were the origins and foundation of all social and legal relations, consolidated the obligation of the state to protect the rights and freedoms, having created the necessary prerequisites for the formation of the society requirements to secure the rights and freedoms, with gradual addition of new principles and institutions to guarantee these rights and freedoms.
Genesis of the Guarantees of the Human Rights and Freedoms of Citizens in Ukraine: Historical and Legal Aspects
Keywords: гарантії прав і свобод людини і громадянина; Україна; історико–правове дослідження; guarantees of human rights and freedoms of citizens; Ukraine; historical and legal research